On Jan 20, 9:17 am, Albert <albert.xtheunkno...@gmail.com> wrote: > It has to be the same otherwise I can't write: > > cosx / (1-sinx) = (1+sinx)/cosx > (cos^2)x = (1+sinx)(1-sinx) > ..``..``.= 1 - (sinx)^2 > (sin^2)x + (cos^2)x = 1
You should never write (sin^2)x to mean sin^2(x).
I have never seen the notation (sin^2)x and I have no idea what it might mean, except as a mistake for sin^2(x).
I do not like sinx. With single-term arguments it is permissible to omit the brackets, but in that case you should in plain-text leave a space -- as in sin x and (sin x)^2.